EFFECTIVE UTILIZATION OF WATER CONSUMPTION USING COMMUNITY WATER SUPPLY ANALYTICS SYSTEM FOR SUSTAINABLE RESOURCE MANAGEMENT (CAHIERS MAGELLANES-NS, 2024)
New methods of improving sustainability and conservation are required due to the increasing demand for water resources in metropolitan areas. "HydroInsight," a complex analytics system intended to track, evaluate, and improve community water usage, is presented in this little project. HydroInsight seeks to provide communities with practical insights for sustainable resource management by fusing cutting-edge technologies and data-driven techniques.